Direct TEM observation of α/γ interface migration during cyclic partial phase transformations at intercritical temperatures in an Fe-0.1C −0.5Mn alloy. (1st October 2019) - Nutter, J.; Farahani, H.; Rainforth, W.M.; van der Zwaag, S.
Abstract: The kinetic behaviour of austenite/ferrite interfaces in a low carbon – 0.5 mass% Mn containing steel during Cyclic Partial Phase Transformation (CPPT) experiments has been investigated using hot stage Transmission Electron Microscopy (TEM). Individual interfaces were observed to display behaviour typical of CPPT experiments as recorded in macroscopic dilatometry experiments and demonstrated i) the "normal", ii) inverse transformations and iii) a stagnant stage in which the interface migrates at a very low velocity as a result of the interface passing through a Mn enriched zone due to the preceding transformation. The length of the stagnant stage determined from the TEM observations shows excellent agreement with that measured from dilatometry and kinetic modelling, whilst the distance migrated from the interface shows some disparities which are primarily attributed to differences in assumptions about grain geometry and nucleation. No special interface features were observed when the interface changed direction and passed through the previously Mn-enriched zones. General observations on the interaction of the transformation interface with microstructural features are also reported. Graphical abstract: Image 1